2012
DOI: 10.3109/09546634.2011.649690
|View full text |Cite
|
Sign up to set email alerts
|

An open, comparative study of 10% potassium hydroxide solution versus salicylic and lactic acid combination in the treatment of molluscum contagiosum in children

Abstract: 10% KOH solution and SAL + LAC combination were found to be equally effective in the treatment of MC in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
3
18
0
3
Order By: Relevance
“…Ten percent of KOH solution versus salicylic and lactic acid combination were equally effective in MC treatment (9).…”
Section: Resultsmentioning
confidence: 91%
“…Ten percent of KOH solution versus salicylic and lactic acid combination were equally effective in MC treatment (9).…”
Section: Resultsmentioning
confidence: 91%
“…Common side effects include irritation, pruritus, burning, and peeling of the skin. Four studies have investigated the use of salicylic acid for the treatment of MC in a total of 190 patients , comparing its efficacy with that of other agents. A study of 26 patients 2 to 12 years of age found no difference in MC resolution between 10% potassium hydroxide (KOH) and a salicylic acid–lactic acid 16.7% combination solution over 6 weeks .…”
Section: Salicylic Acidmentioning
confidence: 99%
“…Four studies have investigated the use of salicylic acid for the treatment of MC in a total of 190 patients , comparing its efficacy with that of other agents. A study of 26 patients 2 to 12 years of age found no difference in MC resolution between 10% potassium hydroxide (KOH) and a salicylic acid–lactic acid 16.7% combination solution over 6 weeks . When reviewing the use of 10% polyvinylpyrrolidone iodine as adjunct with 50% salicylic acid plaster versus salicylic acid plaster monotherapy or 10% polyvinylpyrrolidone–iodine monotherapy in 20 young children, no significant difference in MC resolution was found between the treatment groups.…”
Section: Salicylic Acidmentioning
confidence: 99%
“…9 também comparou os resultados do uso de KOH 10%, combinação de ácido salicílico e láctico e curetagem, sendo a curetagem mais rápida, porém igualmente eficaz à combinação de ácido láctico e salicílico. A conclusão sobre a eficácia de KOH 10% comparado a ácido salicílico combinado a ácido lático foi a mesma que em Köse et al 26 Stephenson et al 27 relataram eficácia parecida entre as soluções e fácil aplicação, apresentando resolução de uma a cinco semanas, podendo causar ardor, eritema, prurido, dor, formação de crostas, hiperpigmentação e erosão como efeitos adversos. O estudo de Uçmak et al 28 também mostrou semelhança na efetividade, porém relatou que KOH a 2,5% apresentou melhores resultados em face.…”
Section: Características Dos Estudos Relatados Nos Artigos E a Classiunclassified